1989
DOI: 10.1021/la00088a021
|View full text |Cite
|
Sign up to set email alerts
|

Reverse micelles of Aerosol-OT in benzene. 4. Investigation of the micropolarity using 1-methyl-8-oxyquinolinium betaine as a probe

Abstract: The aggregation and the micropolarity of Aerosol-OT reverse micelles in benzene are investigated by using a new absorption probe, l-methyl-8-oxyquinolinium betaine (QB) at 25 °C, as a function of the surfactant concentration and the water content of the solutions. QB is preferentially partitioned (>500:1) in the aqueous pool of the aggregates, and its transition energy £qB is shown to have a linear relationship with Kosower's Z values and Dimroth et al. 's ET(30) values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 0 publications
2
60
0
4
Order By: Relevance
“…Since it is known that for RM media the CMC values depend on the method used for their determination, it is customary to define this concentration as the operational CMC. [22,23,45] The values found using QB were similar to other CMC values obtained for water/NaDEHP/toluene systems using very different techniques. [11,17] Comparing the CMC values for NaDEHP and AOT (Table 1) at the same W 0 value, it can be seen that the CMC is lower for AOT than for NaDEHP RMs.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Since it is known that for RM media the CMC values depend on the method used for their determination, it is customary to define this concentration as the operational CMC. [22,23,45] The values found using QB were similar to other CMC values obtained for water/NaDEHP/toluene systems using very different techniques. [11,17] Comparing the CMC values for NaDEHP and AOT (Table 1) at the same W 0 value, it can be seen that the CMC is lower for AOT than for NaDEHP RMs.…”
Section: Resultssupporting
confidence: 82%
“…The neat isosbestic point at l = 555 nm detected at W 0 = 1 (Figure 1) suggests that an equilibrium between free QB in toluene and QB bound to the micelle interface is established. [41][42][43][44][45] On the other hand, Figure 2 shows that this equilibrium is absent when the water content is equal to 10. Similar results were obtained for AOT RMs at this W 0 value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ueda et al (6) found an isosbestic point at 540 nm when they studied QB in dry AOT-benzene solution at several different AOT concentrations. They have attributed the presence of the isosbestic point to the existence of two spectrophotometrically distinguishable states of QB in solution: one in the bulk hydrophobic environment and the other solubilized in the polar interior of the reversed micelles.…”
Section: Introductionmentioning
confidence: 99%
“…A concentration of QB (1 1 10 04 M) significantly lower than surfactant concentration is considered as a probe not to perturb systems (14). QB dissolves in aqueous PFHA micellar media, giving a nearly colorless solution.…”
Section: Uv-vis Absorption Resultsmentioning
confidence: 99%